2017
DOI: 10.1002/2017ja023904
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous observations of traveling convection vortices: Ionosphere‐thermosphere coupling

Abstract: We present simultaneous observations of magnetosphere‐ionosphere‐thermosphere coupling over Svalbard during a traveling convection vortex (TCV) event. Various spaceborne and ground‐based instruments made coordinated measurements, including magnetometers, particle detectors, an all‐sky camera, European Incoherent Scatter (EISCAT) Svalbard Radar, Super Dual Auroral Radar Network (SuperDARN), and SCANning Doppler Imager (SCANDI). The instruments recorded TCVs associated with a sudden change in solar wind dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 59 publications
4
18
2
Order By: Relevance
“…The peak enhancement of 300 K occurred at 200 km. This increase was of smaller magnitude than the radar data presented in Kim et al (), which showed a significant enhancement of 1000–3000 K between 200 and 300 km, and the PFISR data from Zou et al (), which showed an increase of 500–1000 K between 150 and 450 km. The enhancement of the electron temperature also appeared to last longer than the ion temperature enhancement in the PFISR observations.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…The peak enhancement of 300 K occurred at 200 km. This increase was of smaller magnitude than the radar data presented in Kim et al (), which showed a significant enhancement of 1000–3000 K between 200 and 300 km, and the PFISR data from Zou et al (), which showed an increase of 500–1000 K between 150 and 450 km. The enhancement of the electron temperature also appeared to last longer than the ion temperature enhancement in the PFISR observations.…”
Section: Discussioncontrasting
confidence: 60%
“…The peak enhancement of 300 K occurred at 200 km. This increase was of smaller magnitude than the radar data presented in Kim et al (2017), which showed a significant enhancement of 1000-3000 K between 200 and 300 km, and the PFISR data from Zou et al (2017), which showed an increase of 500-1000 K between 150…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Note that such rapid changes in the solar wind could trigger the travelling convection vortices in the ionosphere (e.g., Friis-Christensen et al, 1988;Kim et al, 2017). We start with the solar wind and IMF data, which are presented in Figures 2a-2c for the period 6:00-9:00 UT.…”
Section: Observationsmentioning
confidence: 99%
“…They include three major mechanisms. First, dynamic solar wind pressure events are a major source of traveling convection vortices (TCVs; Kim et al, 2017;Murr & Hughes, 2003;Shi et al, 2014;Sibeck et al, 1989). Second, Kelvin-Helmholtz waves (KHWs) can grow at the magnetopause velocity shear layer and are a very common phenomenon at the magnetosphere boundary particularly during northward IMF condition (Kavosi & Raeder, 2015;Lin et al, 2014).…”
Section: Observations Overviewmentioning
confidence: 99%